Dimensions of suffering and the need for palliative care: experiences and expectations of patients living with cancer and diabetes and their caregivers in Mexico – a qualitative study - Svetlana V Doubova; Ingrid Patricia Martinez-Vega; Felicia Knaul; Afsan Bhadelia; Diana Pérez-Moran; Nancy García-Cervantes (BMJ Open)
Objectives Over 40 million people in low-income and middle-income countries (LMICs) experience serious health-related suffering (SHS) annually and require palliative care. Patient and caregiver experiences of SHS in LMICs are understudied despite their importance in guiding palliative care provision. Diabetes and cancer are the second-leading and third-leading causes of death in Mexico, causing a significant SHS burden on patients, families and health systems. This study examines SHS and palliative care from the point of view of patients with cancer and diabetes and their caregivers.Design A qualitative descriptive study based on in-depth telephone interviews was conducted between August 2021 and February 2022. Data were analysed through inductive thematic analysis.Participants Overall, 20 patients with end-stage cancer, 13 patients with diabetes and 35 family caregivers were interviewed individually.Setting Participants were recruited from two family medicine clinics and a pain clinic in Mexico City.Results Seven themes emerged: (1) suffering as a multifaceted phenomenon, (2) diversity in perceptions of suffering, (3) different coping strategies, (4) need and perceived importance of relief from suffering, (5) barriers to accessing services to relieve suffering, (6) demand for the health sector’s active and humane role in addressing suffering and (7) preferences and need for comprehensive care for relief from suffering. The primary coping strategies included family companionship, protective buffering and faith-based support. Participants lacked knowledge of palliative care. They expressed the importance of relief from suffering, viewing it as the health sector’s responsibility and requesting more humane, personalised care and access to medicines and pain clinics.Conclusions The multifaceted nature of SHS highlights the health system’s responsibility to provide high-quality palliative care. Policies to enhance access to palliative care should integrate it into primary care, redesigning services towards patient and caregiver biopsychosocial and spiritual needs and ensuring access to medicines and competent health personnel.